ISLAMIC PARTIES AND THE VOTING BEHAVIOR OF CITY MUSLIMS IN WEST SUMATRA - Putra, Heru Permana (Jurnal Politik Pemerintahan Dharma Praja, 2023)
The background of this research is that there are no parties based on Islamic values ​​that dominate the victory in the legislative elections in West Sumatra, especially in the three cities that will be the locations of this research. Where the cities are Padang City, Bukittinggi City, and Pariaman City. These three cities have a very dominant Muslim voting population, but in the implementation of legislative elections, not a single party based on Islamic values ​​was able to dominate the victory in the legislative elections. The Muslim community in this city is very synonymous with the policies of its government which are based on sharia, but their voting behavior in legislative general elections does not reflect behavior that supports parties that uphold Islamic teachings. This study uses the theory of voting behavior with a psychological school, to see how the characteristics of voters in this city's Muslim community use a voting behavior approach based on psychological aspects, with the independent variables Issues in the Campaign (X.1) Identification of parties (X.2) and Orientation towards candidates ( X.3) with the dependent variable, namely the voting behavior of urban Muslim communities in general elections. This research uses a quantitative approach with a survey research design, this type of research is explanatory research. Data was collected by distributing questionnaires, respondents were selected using the probability sampling method, namely, stratified random sampling and simple random sampling and using random numbers in determining the respondents. The analysis model for this research is a frequency table and hypothesis testing using Chi Square. The findings of the data in the field show that in measuring the influence between the voting behavior of urban Muslim communities on party identification (X) and voting behavior (Y), the results of this study found that there was a relationship between the identification of Muslim voters' parties on voting behavior of urban Muslim communities in general elections.